Enzyme‐Polymer Conjugates for Tuning, Enhancing, and Expanding Biocatalytic Activity. (11th January 2023) - Heredero, Marcos; Beloqui, Ana
Abstract: Combining polymers with functional proteins is an approach that has brought several successful stories in the field of biomedicine with PEGylated therapeutic proteins. The latest advances in polymer chemistry have facilitated the expansion of protein‐polymer hybrids to other research areas such as biocatalysis. Polymers can impart stability and novel functionalities to the enzyme of interest, thereby improving the catalytic performance of a given reaction. In this review, we have revisited the main methodologies currently used for the synthesis of enzyme‐polymer hybrids, unveiling the interplay between the configuration and the composition of the assembled structure and the eventual traits of the hybrid. Finally, the latest advances, such as the assembly of polymer‐based chemoenzymatic nanoreactors and the use of deep learning methodologies to achieve the most suitable polymer compositions for catalysis, are discussed. Abstract : Assorted tools have been developed in recent years to improve the robustness of biocatalysts, and thereby extend their usefulness, by making use of tailored polymers. This review tackles the use of polymer chemistry approaches, combined with conjugation chemistries, computational modeling, and machine learning tools have led to enzyme‐polymer hybrids with unprecedent added value.